The engineer's project delivery method primer : uniform definitions and case studies - Gransberg, Douglas D.; Loulakis, Michael C.; Gad, Ghada Moustafa (ASCE Press Ser., 2022)
"Authors Gransberg, Loulakis, and Gad define prevalent terms in the US design and construction industry and provide diagrams that explain the Big Three fundamental project delivery methods, visually displaying each method's contractual relationships between the owner, design, and contractor"--